Pharmacogenetics-based population pharmacokinetic analysis of gabapentin in patients with chronic pain: Effect of OCT2 and OCTN1 gene polymorphisms - Yamamoto, Priscila A. [UNESP]; Benzi, Jhohann R. L.; Azeredo, Francine J.; Dach, Fabíola; Ianhez Júnior, Edgar; Zanelli, Cleslei F. [UNESP]; de Moraes, Natália V. [UNESP] (Wiley, 2019)
Gabapentin (GAB) is eliminated unchanged in urine, and organic cation transporters (OCT2 and OCTN1) have been shown to play a role in GAB renal excretion. This prospective clinical study aimed to evaluate the genetic polymorphisms effect on GAB pharmacokinetic (PK) variability using a population pharmacokinetic approach. Data were collected from 53 patients with chronic pain receiving multiple doses of GAB. Patients were genotyped for SLC22A2 c.808G>T and SLC22A4 c.1507C>T polymorphisms. Both polymorphisms' distribution followed the Hardy-Weinberg equilibrium. An one-compartment model with first-order absorption and linear elimination best described the data. The absorption rate constant, volume of distribution, and clearance estimated were 0.44 h −1 , 86 L, and 17.3 × (estimated glomerular filtration ratio/89.58) 1.04  L/h, respectively. The genetic polymorphism SLC22A4 c.1507C>T did not have a significant influence on GAB absorption, distribution or elimination. Due to the low minor allelic frequency of SLC22A2 c.808G>T, further studies require higher number of participants to confirm its effect on GAB renal elimination. In conclusion, GAB clinical pharmacokinetics are strongly influenced by renal function and absorption process, but not by the OCTN1 (SLC22A4 c.1507C>T) polymorphism.
Keywords: chronic pain; gabapentin; genetic polymorphism; population pharmacokinetics